PENGARUH PENERAPAN STRATEGI PEMBELAJARAN SPOTLIGHT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII MTsN PAKAN RABAA KABUPATEN SOLOK SELATAN TAHUN PELAJARAN 2012/2013 - Sari, Yulia Ratna; Sumarmin, Ramadhan; Maizeli, Annika (Pendidikan Biologi, 2013)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  ABSTRACT Â Â Â Â Â Â Â Â Â Â  The lack of students understanding of the topic of biology that presented by teacher lead them to get low achievement. This case can see from the students average learning outcomes ofÂ  biology at MTsN Pakan Rabaa grade seven which gotten score below Minimum Completeness Criteria ( MCC ). One of reason is less of motivation students to study because learning process only dominate by the teacher therefore students often make noisy in the classroom. Interaction between students and teacher is not condusive or there is no feedback between them, beside that the topic is too dificult to understand. To solve this problem, the researcher used Spotlight strategy to apply. This research is experiment which usedÂ  Randomized Control â Group Postest Only Design. The population is all of students at MTsN Pakan Rabaa grade seven academic year 2012/2013 which consist of three classes. Sampling technique that used purposive sampling technique and that chosen as the experimental class are a class VII A and control class VII B. Instrument in this study is a test of student learning outcomes and obtained an average value of 76.40 experimental class and control class 56.27. Based on the analysis of data obtained by the price that has been done tcount = 6.47 > ttable = 1.88 it means that the research hypothesis H1 is accepted. Therefore Spotlight strategy can improve learning outcomes of biology at MTsN Pakan Rabaa grade seven.